Effect of electrical stimulation on functional recovery of lower limbs in patients after anterior cruciate ligament surgery: a systematic review and meta-analysis - Jing Zhang; Wenjing Shan; Rizhao Pang; Tingting Zheng (BMJ Open)
Objectives This study aimed to summarise the existing literature about enhancing muscle strength, lower limb function and self-reported function by electrical stimulation (ES) relative to conventional physical therapy following anterior cruciate ligament reconstruction (ACLR), and to assess the comprehensive treatment effects of ES via meta-analysis.Design Systematic review, meta-analysis.Methods This study systematically searched five electronic databases (PubMed, Web of Science, Scopus, Embase and Chinese National Knowledge Infrastructure), covering records from their inception until February 2024, adhering to a predefined search strategy. Two independent reviewers extracted and synthesised the relevant data using RevMan software (V.5.3). Due to identified heterogeneity, a random-effects model was applied for the meta-analysis. The meta-analysis calculated the effect sizes concerning lower limb function outcomes as standardised mean differences (SMD) with 95% CIs. The methodological quality of the included studies was assessed by the Physiotherapy Evidence Database scale.Results A total of 15 studies involving 1583 patients (between the ages of 15 and 50 years) were included. Meta-analysis results indicated that the ES group could improve the lower limb comprehensive function compared with the control group (CG) based on four clinical tests: the muscle strength (SMD=0.55, 95% CI 0.14 to 0.95, p=0.008, I2=74%), the range of motion (SMD=1.10, 95% CI 0.40 to 1.79, p=0.002, I2=89%), the Lysholm scale (SMD=1.05, 95% CI 0.36 to 1.73, p=0.003, I2=91%) and the visual analogue scale (SMD=0.87, 95% CI 0.38 to 1.37, p=0.006, I2=75%). However, there were no significant differences between the CG and the ES group in terms of leg circumference (SMD=0.61, 95% CI −0.78 to 2.00, p=0.39, I2=87%).Conclusions Adjunctive ES has the potential to enhance early-phase ACLR rehabilitation outcomes, particularly by improving muscle strength, lower limb function and self-reported function, despite the use of different ES modalities.PROSPERO registration number CRD42024549752.